2
$\begingroup$

Given an inhomogeneous wave equation on the whole line \begin{align} &u_{tt}-c^2u_{xx}=f(x,t),\\ &u(x,0)=0,\\ &u_t(x,0)=0. \end{align} The solution formula is \begin{equation} u(x,t)=\frac{1}{2c}\int_{0}^{t}\int_{x-c(t-s)}^{x+c(t-s)}f(y,s)\,dy\,ds. \end{equation} I have trouble with the derivation of the above formula. I wrote the wave equation as $$u_t+cu_x=v,\,v_t-cv_x=f.$$ It follows that \begin{align} &u(x,t)=\int_{0}^{t}v(x-ct+cs,s)\,ds,\\ &v(x,t)=\int_{0}^{t}f(x+ct-cs,s)\,ds. \end{align} Then I substituted $v(x,t)$ into $u(x,t)$ but I am unable to get the solution formula after changing the variables. In particular, I have computed the Jacobian to be $\frac{1}{2c}$ but I am unable to get the upper and lower limits of the integral.

$\endgroup$
1
$\begingroup$

You probably failed to reverse the order of integration. Change the integration variable to $r$ on the $u$ integration:

$$u(x,t)=\int_{0}^{t}v(x-ct+cr,r)\,dr$$ and substitute in the expression for $v$:

$$v(x-ct+cr,r)=\int_{0}^{r}f(x-ct+cr+cr-cs,s)\,ds = \int_{0}^{r}f(x-ct-cs+2cr,s)\,ds.$$

Then

$$u(x,t) =\int_{0}^{t}\int_{0}^{r}f(x-ct - cs +2cr,s)\,dsdr$$

But note in this expression that we are integrating with $s$ first, then with $r$ second. But in your target form, the integration is $y$ first, $s$ second. So we need to reverse the order. In this form, $0 \le r \le t$ and $0 \le s \le r$. So $r$ and $s$ can vary from $0$ to $t$, but always $r \ge s$. If we choose $s$ first, then $s \le r \le t$ are the limits on $r$: $$u(x,t) =\int_{0}^{t}\int_{s}^{t}f(x-ct - cs +2cr,s)\,drds$$

Now you will find that the substitution $y = x-ct - cs +2cr$ gives the correct limits.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.